Evripidis fabvlae. Tomvs I : cyclops -- Alcestis -- Heraclidae -- Hippolytvs --Andromacha -- Hecvba - Ευριπίδης, 480-406 π.Χ. (OXONII, 1963)
Κύκλωψ (kyclops) - 'λκηστις (Alcestis) - Μήδεια (Medea) - Ηρακλείδαι (Heraclidae) - Ιππόλυτος ( Hippolytvs) - Ανδρομάχη (Andromacha) - Εκάβη (Hecvba)